Dampak Gangguan Siklus Sirkadian terhadap Kualitas Hafalan Santri Penghafal Al-Qur’an di TPQ Riyadhul Mubarok - Khidir, Achmad Khidir Afandi; Hilma, Hilma Alifah Baskoro; Syifa Mulyani Andini (Jurnal Kesehatan Qamarul Huda, 2025)
The circadian cycle is a cycle that regulates the body's biological clock such as sleeping and waking. This cycle regulates the body's alertness and response to the environment, especially light. The circadian cycle is influenced by several factors, namely light, temperature and radiation. Busy activities and high demands also affect the internal circadian cycle. Especially for students who memorize the Koran and are active students who have multiple activities and have high demands. The memorizers of the Al-Qur'an at TPQ Riyadhul Mubarok have circadian cycle disorders which affect the quality of their memorization. This is of course caused by a disturbed sleep cycle and is an important activity for the body to function properly.